Manual versus femtosecond laser-assisted relaxing incisions for correction of low astigmatism in implantable collamer lens surgery - Ling Zhou; Qizhi Zhou; Andrea Llovet-Rausell (Indian Journal of Ophthalmology)
Purpose: To compare the safety, efficacy, and stability of astigmatism correction with manual versus femtosecond laser-assisted limbal relaxing incisions (LRIs) during implantable collamer lens (ICL) surgery. Design: Observational case-series. Methods: Charts of myopic patients with astigmatism <1.75D who underwent ICL implantation combined with manual or FL-assisted LRIs were retrospectively reviewed. Uncorrected and corrected distance visual acuities (UDVA, CDVA), refraction, and astigmatism parameters were evaluated at 1 month and 1 year postoperatively. Results: From a total of 46 eyes of 32 patients, 19 eyes had FL-assisted LRIs (FLLRI group) and 27 had manual LRIs (MLRI group). The mean UDVA and CDVA improved after surgery in both groups. The FLLRI group showed a higher reduction in the mean manifest astigmatism from −1.00 ± 0.09D to −0.33 ± 0.05D at 1 month (P < 0.01) and −0.41 ± 0.07D at 1 year (P = 0.05), compared with MLRI group (from −1.30 ± 0.08D to −0.75 ± 0.10D and −0.82 ± 0.09D). Surgically induced astigmatism (SIA) remained stable in the FLLRI group (0.71 ± 0.09D to 0.63 ± 0.08D, P = 0.15) and MLRI group (0.65 ± 0.06D to 0.55 ± 0.06D, P = 0.14) at 1 year. No differences in SIA were found between groups. The difference vector (DV) was lower in the FLLRI group at 1 month and 1 year (0.33 ± 0.05D vs 0.75 ± 0.10D, P < 0.01; 0.40 ± 0.07D vs 0.82 ± 0.09D, P = 0.046). Correction index (CI) was <1 in both groups, meaning undercorrection. Success index in the FLLRI group at 1 month was better compared with the MLRI group (0.43 ± 0.08 vs 0.71 ± 0.10, P = 0.009). Conclusions: FLRIs and MLRIs are safe and effective methods in reducing corneal astigmatism during ICL surgery. FLLRIs display better astigmatism correction than MLRIs.